ANALISI PELAKSANAAN FUNGSI DAN WEWENANG BADAN PERMUSYAWARATAN KEPENGHULUAN Studi Kasus Kepenghuluan Pujud Kecamatan Pujud Kabupaten Rokan Hilir - Rudi Hartono; Febri Yuliani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Organization is a means or instrument achieving goals . Therefore, the organization is said to be a container or vehicle , the activities of people who work together to achieve goals . In container activity that everyone had a clear assignment of authority and responsibility , relationships and governance work . Further Consultative Body Kepenghuluan organization that is one element of government at the level of kepenghuluan , whose membership consists of representatives of concerned residents kepenghuluan defined by means of Deliberation and Consensus . What is meant by a representative masyawarakat in this case as the Chairman Pillars of Citizens , indigenous stakeholders and community leaders that serves to protect the customs, making the rules , and share their aspirations of society , and of the functions of the Consultative Body tersbut kepenghuluan Pujud Kepenghuluan in Rokan Hilir district Pujud districts have authority discuss the draft regulations kepenghuluan with the prince , to supervise pelaksnaan kepenghuluan rules and regulations of the prince , propose the appointment and dismissal of the prince , the prince of the selection committee formed , digging , accommodating , collect , formulate and channel the aspirations of the people , and arrange the order of kepenghuluan consultative body . So far Consultative Body Kepenghuluan in kepenghuluan Pujud Rokan Hilir subdistrict district Pujud not maximized in carrying out its functions and authority as a check and balance between the government and the public Kepenghuluan .The purpose of this study is based on research problems is to know how the Implementation of Functions and Powers of the Agency Consultative Pujud kepenghuluan Kepenghuluan in Rokan Hilir district Pujud districts .Theoretical concept used is the theory of functions and powers according to Prof. Kepenghuluan Consultative Body or Village Consultative Body . Drs . HAW . Widjaja . The indicators in this study is Pengayoman , Legislation , Supervision , and the community and share their aspirations . With descriptive qualitative research methods , and research sites in Kepenghuluan Pujud Pujud Rokan Hilir with key informant penghoeloe , Kepenghuluan device , the Chairman and Members of the CPC , as well as community leaders .From the results, it can be concluded that in carrying out its functions and authority Kepenghuluan Consultative Body in kepenghuluan Pujud districts Pujud Downstream Roak district is not maximized as they should be in accordance with the functions and authority of the Kepenghuluan Consultative Body , namely , nurturing , legislation , oversight , and share their aspirations as people who have mandated in Rokan Hilir Regency Regulation No. 04 Year 2009 on Kepenghuluan Consultative Body .Keywords : Analysis , Function and Powers , Kepenghuluan Consultative Body